The Golden Age of the Quantity Theory. - Laidler, David E. W. (Princeton : Princeton University Press, 2014)
How did neoclassical monetary economics, as epitomized by the work of Fisher, Wicksell, and the Cambridge School, evolve from the classical orthodoxy that dominated economics in the 1870s? To answer this question, David Laidler considers the interaction of theoretical developments with contemporary policy debates about bimetallism and the evolution of the gold exchange standard. He argues that neoclassical monetary economics, in which the quantity theory of money played a central role, laid the intellectual groundwork for the replacement of the gold standard by various managed monetary syst.
Cost of Production and the Quantity TheoryCredit and the Velocity of Money; Interest Rates and Inflation; The Cumulative Process and the Quantity Theory; Empirical Evidence; Wicksell on the Cycle; Wicksell's Legacy; Notes; 6. Neoclassical Monetary Theory and Monetary; Introduction; The Spread of Gold Monometallism; The Mechanics of Bimetallism; Arguments for Gold Monometallism; The International Dimension; Variations on Bimetallism; Indexation; Wicksell on Managed Money; Central Banking; Edgeworth on Banking; Concluding Comment; Notes; 7. A Summing Up; Notes; References; Name Index.
Print version record.
Subject Index.
English.
eBooks on EBSCOhost
Keywords: Quantity theory of money; Neoclassical school of economics; Théorie quantitative de la monnaie; École néoclassique d'économie politique; BUSINESS & ECONOMICS -- Money & Monetary Policy; BUSINESS & ECONOMICS -- Finance; Neoclassical school of economics; Quantity theory of money